Foster Care in the Context of Trends and Changes in the Concept of Parenthood - Škoviera, Albín (My University, 2023)
The author perceives the contexts of contemporary changes through the lens of the problems of children growing up outside their biological family, e.g. in foster care and adoption, but also in various social and educational institutions. It asks whether the best interests of the child are not in fact more likely to be the interests of a specific section of parents with their own interests at heart, or those of adults who are part of ideological lobby groups. It highlights the fact that the upbringing and care of children growing up outside the biological family has a number of legal, ethical, psychological and educational aspects that are complicated to reconcile optimally for the benefit of the child at the present time.
Pěstounská péče v kontextu trendů a změn v pojetí rodičovství
Keywords: parenting; foster care; educational and social institutions; rodičovství; pěstounská péče; výchovné a sociální instituce